Forestry Extension Performance in Enhancing Forest Farmer Knowledge and Skills: A Case Study in Tompobulu, Maros Regency - Imran, Andi Nur; A.Samsu, Andi Khairil; Muliana Djafar, Muliana (Forestry Department, University of Muhammadiyah Makassar, 2024)
Forestry Extension Workers, as one of the important parties in maintaining and preserving forest resources in Indonesia, are expected to have an understanding of good extension methods and techniques so that farmers around the forest can improve their knowledge and skills in managing and utilising forest products. This study aimed to assess the performance of forestry extension workers in Tompobulu District. And also evaluate their role in enhancing the knowledge and skills of forest farmer groups in Maros Regency. It was located in six villages, namely Bonto Somba Village, Bonto Manurung, Bonto Matinggi, Bonto Manai, Tompubulu, and Pucak Maros Regency with the number of samples in the study was 57. The study employed qualitative descriptive analysis using a Likert scale, and quantitative analysis using the t-test. The performance of forestry extension workers that significantly influences increasing the knowledge and skills of forest farmer groups consists of six indicator components, namely: facilitating forest farmer groups to prepare forest product utilisation maps; facilitating forest farmer groups to prepare annual work programs and plans; facilitating forest farmer group members to improve human resource quality; facilitating forest farmer groups to disseminate or spread information on forest product technology; facilitating forest farmer groups to grow their empowerment and independence; and facilitating forest farmer groups to increase production results of superior forest product commodities. Meanwhile, the performance of forestry extension workers that does not significantly influence increasing the knowledge and skills of forest farmer groups is Facilitating Business Partnerships Between Forest Farmer Groups, Entrepreneurs, and the Government, Facilitating Forest Farmer Groups to Access Business Capital with Financial Institutions, Banks, and the Government; and Facilitating Increasing the Income and Welfare of Forest Farmer Groups.